Eric Venbrux: A Death in the Tiwi Islands. Conflict, Ritual and Social Life in an Australian Aboriginal Community - Christensen, Pia Monrad (Tidsskriftet Antropologi, 1999)
Conflict, Ritual and Social Life in an Australian Aboriginal Community Anmeldes af Pia Monrad Christensen